2020
DOI: 10.1001/jamanetworkopen.2020.7940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nocturnal Oxygen Therapy on Nocturnal Hypoxemia and Sleep Apnea Among Patients With Chronic Obstructive Pulmonary Disease Traveling to 2048 Meters

Abstract: IMPORTANCE There are no established measures to prevent nocturnal breathing disturbances and other altitude-related adverse health effects (ARAHEs) among lowlanders with chronic obstructive pulmonary disease (COPD) traveling to high altitude. OBJECTIVE To evaluate whether nocturnal oxygen therapy (NOT) prevents nocturnal hypoxemia and breathing disturbances during the first night of a stay at 2048 m and reduces the incidence of ARAHEs. DESIGN, SETTING, AND PARTICIPANTS This randomized, placebo-controlled cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…At 2,048 m under NOT, one patient experienced a COPD exacerbation. As previously published, NOT significantly reduced the proportion of altitude-related illnesses compared with placebo intervention (8 vs. 1, P < 0.001) ( 15 ). At 2,048 m, patients experiencing an altitude-related illness were treated with oxygen and medication as appropriate and were relocated to low altitude, which led to recovery without sequelae.…”
Section: Resultssupporting
confidence: 60%
“…At 2,048 m under NOT, one patient experienced a COPD exacerbation. As previously published, NOT significantly reduced the proportion of altitude-related illnesses compared with placebo intervention (8 vs. 1, P < 0.001) ( 15 ). At 2,048 m, patients experiencing an altitude-related illness were treated with oxygen and medication as appropriate and were relocated to low altitude, which led to recovery without sequelae.…”
Section: Resultssupporting
confidence: 60%
“…In a previous study with 95 COPD patients exposed to 3,100 m, preventive treatment with dexamethasone showed a significant mitigating effect with a mean difference of −0.5 (−0.9 to −0.1) WU between the placebo and the treatment group (Lichtblau et al, 2019a). The less pronounced and non-significant effect of NOT in the current study might be explained by the fact, that in this study, all measurements were performed on ambient air at 2,048 m after the night with NOT; and thus, a potential vasodilator effect of oxygen may not have persisted anymore, which was already shown in the arterial blood gas analysis published in the main paper where no difference was found between NOT and placebo at 2,048 m (Tan et al, 2020). Looking more closely at the course of PAP and PVR during acute exposure to hypoxia reveals that an excess increase occurs within the acute phase (<180 min) as described in vitro and in vivo, followed by a dip and a steady increase over the next hours (Sommer et al, 2016).…”
Section: Discussionmentioning
confidence: 54%
“…Adult patients (18-75 years) diagnosed with COPD GOLD grades 2-3 permanently living < 800 m were included. Exclusion criteria were hypoxemia defined as oxygen saturation by pulse oximetry (SpO 2 ) lower than 92% at 490 m, home oxygen or continuous positive airway pressure (CPAP) therapy, any uncontrolled cardiovascular disease, or history of obstructive sleep syndrome (Tan et al, 2020). Patients were monitored with an online sleep study with camera view during the night, ensuring compliance.…”
Section: Patientsmentioning
confidence: 99%
“…However, the role of this hypoxia-altitude-simulating test has never been established, as the degree of deoxygenation during the test hast not been shown to predict symptoms at real altitude ( 33 ). In line with this, a currently published trial has shown that 16% of moderate to severe COPD patients, who did not fulfill the criteria to perform a hypoxia-altitude simulation test, revealed severe deoxygenation at 2,048 m of real altitude ( 22 ).…”
Section: Discussionmentioning
confidence: 76%
“…Apneas/hypopneas were scored when there was a reduction of nasal pressure swings or the inductive plethysmographic sum signal to <50% of baseline for >10 s, as described previously ( 19 – 21 ) (Transient reductions in breathing amplitude to <50% of baseline for 5–10 s were also scored as apneas/hypopneas if they occurred as part of a periodic breathing pattern with hyperventilation alternating with central apneas/hypopneas for at least three consecutive cycles.). The apnea/hypopnea index (AHI) was computed as the number of events per hour of total sleep time and time in bed; the oxygen desaturation index (ODI, > 3% SpO 2 dips) was computed as the number of events per hour of time in bed as described previously ( 22 ).…”
Section: Methodsmentioning
confidence: 99%